30-Year-Long Changes in Terrestrial Vertebrate Fauna of Niebieskie Źródła (Blue Springs) Nature Reserve in Tomaszów Mazowiecki, Central Poland - Wojciechowski, Zbigniew; Markowski, Janusz; Janiszewski, Tomasz; Hejduk, Janusz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2010)
The article focuses on changes in terrestrial vertebrate fauna of Niebieskie Źródła (Blue Springs) Nature Reserve that occurred between two censuses carried out in the area. The first census was carried out in the period of 1968-1970, and the second census in the period of 1998-1999. In 1998-1999 the occurrence of four species of amphibians, 41 of birds and 15 of mammals was recorded. In comparison with investigations from 1968-1970 two species of amphibians, two species of mammals, and nine species of birds were found to have disappeared from the reserve. In the census carried out in 1998 and 1999 we recorded 22 new species of vertebrates: one new species of amphibian, five species of mammals, and 16 species of birds. The recent observations showed a decline in the abundance of amphibian species in the reserve, especially in the closest vicinity to the urban development around the city of Tomaszów Mazowiecki. The quantitative data on birds showed an increase in the numbers and abundance, which was mainly pronounced in the group of forest species, especially cavity and shrub nesters. We suggest that these changes are directly related to the succession of forest vegetation and its developing vertical structure, as well as to an increase in the forestation of the reserve area.